Developing a Framework to Increase Access to Mental Health Services for Children With Special Needs in Ethiopia - Hughes, Tammy L.; Quinn, Cydney; Tiberi, Amy; Zeleke, Waganesh A. (Frontiers in Sociology, 2020)
The availability and accessibility of state-of-the-art diagnostic processes and evidence-based treatments are limited in developing countries such as Ethiopia (Hohenshil et al. 2013; Kakuma et al. 2011; Wondie 2014; Zeleke, Hughes, & Chitiyo, 2017). Similar to other developing nations, there is a lack of foundational services for mental practices to build on and that are well suited to the culture (Wondie, 2014). Whereas Western cultures generally follow the biomedical model of disease, non-Western culture, such as that of Ethiopia, adheres to traditional and religious views to explain the origin of mental illness (Jacobsson & Merdasa, 1991; Kortmann, 1987). More specifically, mental health problems may be attributed to supernatural causes or other spiritual crises rather than a combination of biopsychosocial influences. Due to such perceptions, the help-seeking behavior of Ethiopians with mental health and well-being challenges are mostly limited to family, friends and local community healers rather than professional help (Zeleke, Hughes, & Chitiyo, 2017). In order to promote mental health and well-being among its citizens, we recommend practical steps to building evidence based practices that are integrated into existing culturally relevant traditions.